2018
DOI: 10.3390/en11113151
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Modelling and Simulation of an Inclined Horizontal Axis Hydrokinetic Turbine

Abstract: In this contribution, unsteady three-dimensional numerical simulations of the water flow through a horizontal axis hydrokinetic turbine (HAHT) of the Garman type are performed. This study was conducted in order to estimate the influence of turbine inclination with respect to the incoming flow on turbine performance and forces acting on the rotor, which is studied using a time-accurate Reynolds-averaged Navier-Stokes (RANS) commercial solver. Changes of the flow in time are described by a physical transient mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(54 reference statements)
0
7
0
1
Order By: Relevance
“…It is also worth noting that in nearly all consulted papers the authors carried out their numerical studies in horizontal axis turbines with rotor perpendicular to the water flow, leaving without answer how is the behavior of the flow around a turbine with inclined axis and hence its performance. However, some experimental studies [91,92] and a numerical study [49] about the effects of changing blade pitch and shaft inclination angle reported an average power coefficient around 30%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that in nearly all consulted papers the authors carried out their numerical studies in horizontal axis turbines with rotor perpendicular to the water flow, leaving without answer how is the behavior of the flow around a turbine with inclined axis and hence its performance. However, some experimental studies [91,92] and a numerical study [49] about the effects of changing blade pitch and shaft inclination angle reported an average power coefficient around 30%.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, [49] carried out an analysis about the influence of inclined axis on the performance of the HAHT; in this case, three configurations were evaluated: rotor parallel to flow, 15° and 30° inclined rotor. The computational model of the rotor was based on AQUAVATIO turbine [50].…”
Section: Hydrodynamic Design and Performance Analysis Of Hahtsmentioning
confidence: 99%
“…The k-ω SST model is appropriate to compute flows with adverse pressure gradients and boundary layer separation which are flow phenomena commonly found in turbomachinery applications. Contreras et al [26] showed that the k-ω SST turbulence model performs better than the kmodel to predict the power coefficient of hydrokinetic turbines. Hocine et al [16] used the k-ω SST and VOF approach to estimate the performance of a Darrieus hydrokinetic turbine; the computed power coefficient showed the highest discrepancy with experimental data (13%) near its maximum value.…”
Section: Governing Equationsmentioning
confidence: 99%
“…For this reason, this study focuses on the performance of a horizontal-axis water turbine. To understand the flow dynamics and improve the turbine efficiency, computational and experimental approaches have been explored in recent years (Bahaj,[5]; Yan, [6]; Bahaj, [7]; Contreras, [8]). In that sense, Computational Fluid Dynamics (CFD) is an essential approach to analyze the fluid flow through the turbine rotor and to estimate its performance.…”
Section: Introductionmentioning
confidence: 99%